EDUCATION AS A CULTURE OF INTERNATIONAL INTEGRATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Modern socio-economic challenges facing educational systems have a global format, determine the need for an essential transformation of organizational and didactic resources, goal-setting and value-based innovations while effectively preserving the rich heritage of peoples and states and updating promisingly significant components of development, cooperation of various territorial, ethnic entities and other communities. The implementation of these tasks is systemically productive in the conditions of targeted support for individual and corporate creative potential, including cultural and educational potential, producing socially responsible communities, meanings, paths and territories. Social and educational processes are gaining growing importance here
Keywords: сultural and educational integration, territorial entities, international social connections, communities, design and creative actualization, synergy, educational and research activities of students, transpolation of educational technologies.